Acetic Acid‐Assisted Synergistic Modulation of Crystallization Kinetics and Inhibition of Sn2+ Oxidation in Tin‐Based Perovskite Solar Cells. (2nd December 2021) - Su, Yang; Yang, Jia; Liu, Gengling; Sheng, Wangping; Zhang, Jiaqi; Zhong, Yang; Tan, Licheng; Chen, Yiwang
Abstract: Tin‐based halide perovskites attract incremental attention due to the favorable optoelectronic properties and ideal bandgaps. However, the poor crystalline quality is still the biggest challenge for further progress in tin‐based perovskite solar cells (PVSCs) due to the unfavorable defects and uncontrollable crystallization kinetics. Here, acetic acid (HAc) is first introduced to reduce the supersaturated concentration of the precursor solution to preferentially form pre‐nucleation clusters, thus inducing rapid nucleation for effective regulation of crystallization kinetics. In particular, the hydrogen ion and acetate ion contained in HAc can effectively inhibit the oxidation of Sn 2+, and the hydrogen bonding interaction between HAc and iodide ion (I ‐ ) greatly reduces the loss of I ‐, which guarantees the I ‐ /Sn 2+ stoichiometric ratio of the corresponding perovskite film close to theoretical value, thus effectively reducing the defect density and maintaining the perfect crystal lattice. Consequently, the HAc‐assisted tin‐based PVSCs achieve a champion power conversion efficiency of 12.26% with superior open‐circuit voltage up to 0.75 V. Moreover, the unencapsulated device maintains nearly 90% of the initial PCE even after 3000 h storage in nitrogen atmosphere. This demonstrated strategy enables to prepare high‐quality tin‐based perovskite film with lower defect density and lattice distortion. Abstract : Acetic acid (HAc) is first introduced to reduce the supersaturated concentration of the precursor solution to form pre‐nucleation clusters, thus inducing rapid nucleation. In particular, the introduction of HAc can inhibit the oxidation of Sn 2+ and reduce the loss of I ‐ . HAc‐assisted device deliver a champion efficiency of 12.26%, maintaining ≈90% of initial efficiency after storage in nitrogen over 3000 h.